2019
DOI: 10.1136/bmjopen-2018-028373
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of care with a single-entry model of referral for total joint replacement: a preimplementation/postimplementation evaluation

Abstract: ObjectivesWe assessed: (1) waiting time variation among surgeons; (2) proportion of patients receiving surgery within benchmark and (3) influence of the Winnipeg Central Intake Service (WCIS) across five dimensions of quality: accessibility, acceptability, appropriateness, effectiveness, safety.DesignPreimplementation/postimplementation cross-sectional design comparing historical (n=2282) and prospective (n=2397) cohorts.SettingRegional, provincial health authority.ParticipantsPatients awaiting total joint rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Damani et al (35) reported a quasi-experimental study comparing a historical cohort (2397 patients recruited from 1 June 2011 to 1 June 2012) and a prospective cohort (2282 patients from 1 September 2013 to 1 September 2014) to assess the effects of a single-entry model (SEM) of referral to the next-available surgeon for total joint replacement surgeries in Canada. The results showed that the variability of waiting times among surgeons was reduced by 3.7 and 4.3 weeks for hip and knee replacements, respectively and there was a 5.6% increase in patients operated within the benchmark period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Damani et al (35) reported a quasi-experimental study comparing a historical cohort (2397 patients recruited from 1 June 2011 to 1 June 2012) and a prospective cohort (2282 patients from 1 September 2013 to 1 September 2014) to assess the effects of a single-entry model (SEM) of referral to the next-available surgeon for total joint replacement surgeries in Canada. The results showed that the variability of waiting times among surgeons was reduced by 3.7 and 4.3 weeks for hip and knee replacements, respectively and there was a 5.6% increase in patients operated within the benchmark period.…”
Section: Resultsmentioning
confidence: 99%
“…Where there are multiple queues for surgical lists at the same surgery clinic, targeted patient referrals have had variable impacts on waiting times across different specialists. The application of single entry models (SEM) while pooling referrals enabled patients to see the next-available surgeon for their procedure and improved timeliness and e cient patient ow (35). The systematic review for SEM also showed a consistently positive impact on access-related variables for referral of patients to surgical clinics (51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Bad care must be addressed by clinical leaders rather than the marketplace; group models of care actually make it easier to identify variations in practice and to support colleagues to improve the appropriateness and reliability of care and enhance surgeons' work environment. 12 Ultimately, surgeons want to perform operations for their patients. Many feel their careers and livelihoods are threatened by the COVID-19 restrictions on hospital activity.…”
mentioning
confidence: 99%